2007
DOI: 10.1002/elps.200600435
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of poly(methyl methacrylate) microfluidic devices for high‐resolution separations of single‐stranded DNA

Abstract: While polymer-based microfluidic devices offer some unique opportunities in developing low-cost systems for a variety of application areas, the ability to sort electrophoretically with high efficiency a number of different targets has remained somewhat elusive with an example consisting of achieving single base resolution as required for DNA sequencing. While the reasons for this are many-fold, it is clear that some type of coating is required on the polymer substrate to suppress the EOF and/or minimize potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…For instance, Soper’s research group reported formation of a layer of linear polyacrylamide on the channel surfaces of a PMMA device via an amide bond and they achieved high-resolution electrophoretic separation of single-stranded DNA with a single base pair resolution. 64 Polyacrylamide can also be coated on the surfaces of PMMA, COC and polycarbonate via photografting. 32,65 Other materials such as poly(ethylene glycol) (PEG) have also been grafted onto the channel surfaces of a PMMA device for electrophoresis of proteins and peptides.…”
Section: Surface Treatmentmentioning
confidence: 99%
“…For instance, Soper’s research group reported formation of a layer of linear polyacrylamide on the channel surfaces of a PMMA device via an amide bond and they achieved high-resolution electrophoretic separation of single-stranded DNA with a single base pair resolution. 64 Polyacrylamide can also be coated on the surfaces of PMMA, COC and polycarbonate via photografting. 32,65 Other materials such as poly(ethylene glycol) (PEG) have also been grafted onto the channel surfaces of a PMMA device for electrophoresis of proteins and peptides.…”
Section: Surface Treatmentmentioning
confidence: 99%
“…Soper and co-workers [53] have developed a simple grafting procedure to allow the formation of linear polyarcylamides onto a PMMA microfluidic device to suppress the EOF and minimize potential solute-wall interactions. The procedure involved creating an amine-terminated PMMA surface by appropriately functionalizing the PMMA through either a chemical or photochemical process.…”
Section: Covalent Modificationmentioning
confidence: 99%
“…DNA separation is an essential operation in many genetic engineering processes and is commonly performed when executing biochemical and biological analyses (Bown and Meinhart 2006;Das et al 2006;Gutsche et al 2006;Szantai and Guttman 2006;Wang et al 2006Liu et al 2007Llopis et al 2007;Ohashi et al 2007;Prakash and Kaler 2007;Sun et al 2007). However, the conventional slab-gel DNA separation method has a number of drawbacks, including a long separation time, an excessive sample consumption and a low separation efficiency.…”
Section: Introductionmentioning
confidence: 99%